Improving the circuitry of high-precision high-speed acousto-optic laser interferometers of displacements with frequency matching of component blocks and double heterodyning at phototransformation stage - E. V. Leun; A. E. Shakhanov; S. Yu. Samoilov; A. Yu. Kolobov (Омский научный вестник)
The article discusses the development of the circuitry of acousto-optic (AO) laser displacement interferometers (LDI) and the values of resolution and speed of controlled displacements achieved by them. The issues of frequency matching of blocks of AO LDI are discussed: AO modulator, photodetector device (FDD) and frequency generator. The features of phototransformation of the FDD under its illumination by three spatially combined optical streams are studied. Of these, two streams are of different frequencies, created as a result of diffraction in the AO modulator and are used to measure the phase shift from the controlled displacements of the object in the AO LDI. The third optical stream is amplitude-modulated with a frequency close to the difference frequency of the first two optical streams. This technique leads to a twofold transfer (double heterodination) of the phase shift from the offsets to the electrical signal of the difference frequency between the three optical streams. The schemes of AO LDI with a constant value of the frequency of the amplitude-modulated optical flow and with its auto-tuning are considered. The features of the use of cooled FDD in AO LDI are discussed.